COMPARATIVE ANALYSIS OF DATA RECOVERY USING EASEUS DATA RECOVERY WIZARD AND RECUVA APPLICATIONS - Ade Putra; Muhammad Donni Lesmana Siahaan; Arpan Arpan (INFOKUM, 2022)
At the end of the day, the use of computers is intended for data processing in the form of text, images, videos, and data processing that can be carried out easily and quickly. Individual computer users and organizations in everyday life often work and store data on computers, but in reality, there are certain events where the results of work, in the form of document files on the computer, can be lost so that very important and much needed files are lost from the storage media in the computer. computer or laptop. In recovering lost files or documents, various software can be used, including Pandora Recovery, Recuva and EaseUS Data Recovery Wizard. In this study, what will be discussed is the recovery of lost data by comparing the use of the EaseUS Data Recovery Wizard and Recuva application